(untitled) (UNED Research Journal, 2016)
Due to the importance of primary production in the trophic network, most aquatic ecosystems rely on microalgae. However, there are fewer studies on phytoplankton in the Central American region, specifically on marine diatoms, in part because it is difficult to isolate and cultivate local species in tropical climates. The objective of this study is the isolation of two local diatoms of Chaetoceros and Nitzschia, potential food for aquatic organisms. Water samples was taken from the Nicoya Gulf, located in the Central Pacific coast of Costa Rica. The samples were successively filtered first through a 35µm pore size filter and then through one of 20µm. They were repeatedly isolated using modified Pasteur pipettes, and serial dilutions were done until a monoalgal culture was obtained. Two Bacillariophyceae were isolated: NGN1, genus Nitzschia; and CGN2, genus Chaetoceros. This study is a step toward reducing the importation of phytoplankton on feeding aquatic organisms by providing technical and scientific information to develop a microalgal culture from this region.